Selection enhances protein evolvability by increasing mutational robustness and foldability - Zheng, Jia; Guo, Ning; Wagner, Andreas (Science (American Association for the Advancement of Science), 2020)
Mutations generate variability that is either neutral or subject to natural selection. Robustness is a measure of the ability to withstand deleterious mutational effects. Zheng et al. exposed Escherichia coli populations expressing a yellow fluorescent protein to strong, weak, or no selection for yellow fluorescence for four generations. They then selected these populations to a related function, green fluorescence, for four more generations. The strong selection first for yellow and then green fluorescence resulted in the most green fluorescence and the accumulation of the most mutations. This outcome likely was due to the increased foldability of the protein. Selection thus provides a threshold for mutation accumulation, but robustness maintains a buffer necessary for protein evolution. Science , this issue p. eabb5962 Directed evolution of yellow fluorescent protein into green fluorescent protein shows how selection can improve functional evolvability. Natural selection can promote or hinder a population’s evolvability—the ability to evolve new and adaptive phenotypes—but the underlying mechanisms are poorly understood. To examine how the strength of selection affects evolvability, we subjected populations of yellow fluorescent protein to directed evolution under different selection regimes and then evolved them toward the new phenotype of green fluorescence. Populations under strong selection for the yellow phenotype evolved the green phenotype most rapidly. They did so by accumulating mutations that increase both robustness to mutations and foldability. Under weak selection, neofunctionalizing mutations rose to higher frequency at first, but more frequent deleterious mutations undermined their eventual success. Our experiments show how selection can enhance evolvability by enhancing robustness and create the conditions necessary for evolutionary success.